2019
DOI: 10.2217/bmm-2019-0020
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of FUSOBACTERIUM NUCLEATUM and Streptococcus Gallolyticus in Saliva of Colorectal Cancer Patients

Abstract: Aim: The aim of the study was to examine the prevalence and amount of Fusobacterium nucleatum ( Fn), Porphyromonas gingivalis ( Pg) and Streptococcus gallolyticus ( Sg) in the saliva of colorectal cancer (CRC) patients and controls. Methods: PCR analyses performed in 71 CRC patients and 77 controls. Results: Saliva samples of patients had higher amounts of Fn (p = 0.001) and Sg (p < 0.001) compared with controls. Amount of Fn and Sg were lower in the microsatellite instability (+) group. Evaluation of saliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 68 publications
1
25
1
2
Order By: Relevance
“…S1). Similarly, higher amount of F. nucleatum in saliva was found in patients with colorectal cancer (Guven et al, 2019). Interestingly, we have also recently reported that F. nucleatum was highly FIG.…”
Section: Discussionmentioning
confidence: 60%
“…S1). Similarly, higher amount of F. nucleatum in saliva was found in patients with colorectal cancer (Guven et al, 2019). Interestingly, we have also recently reported that F. nucleatum was highly FIG.…”
Section: Discussionmentioning
confidence: 60%
“…As for searching candidate salivary biomarkers, Fn, Pg, Dd and Pm were selected as qPCR targets in our cohort based on previous literatures. One recent study reported that salivary Fn level in CRC group was higher compared with the control group, while the amount of salivary Pg was similar between the two groups 42 . However, the sample size included was limited which need further validation.…”
Section: Discussionmentioning
confidence: 86%
“…This finding also merits further exploration in a larger study. Cohort studies in pancreatic and orodigestive cancers have found increased risk for incidence and mortality with high levels of P. gingivalis antibodies in serum, [1] and similarly high levels of F. nucleatum in saliva appear to be associated with colon cancer risk [40].…”
Section: Discussionmentioning
confidence: 99%